PENGARUH BUDAYA ORGANISASI DAN STRES KERJA TERHADAP KINERJA KARYAWAN PADA PT. SERDANG JAYA PERDANA - Vincent Rivelio; Lidya Wati Pranata; Jessyca Jessyca; Santi Santi; Hendry Hendry (JURNAL PROINTEGRITA, 2019)
This research aims at testing and analyzing the influence of organizational culture and work stress on employees’ performance at PT. SerdangJaya Perdana. The researcher took the object of research from PT. Serdang Jaya Perdana. Employees’ performance can be interpreted as the ability of employees to do their jobs. The performance of an employee is what distinguishes each employee who has different levels of importance in carrying out their duties. Management can measure the company's performance on each employee. Improving employee performance cannot just happen, but there are factors affected such as organizational culture and work stress. The population used is 97 people by taking samples using the Slovin formula and 30 employees to test the validity taken entirely from the rest of the population in the company. The research method used is quantitative, quantitative descriptive research type. Methods of collecting data was done by having interviews, questionnaires and studies. The analytical method used is multiple linear regression, determination coefficient and simultaneous testing (F-Test) with Fcount> Ftable (52,684> 3,11) and partially (t-Test) with values ​​for organizational culture variable t count>ttable number (5,216> 1,99045) and work stress(2.694> 1,99045). The results of the study prove that organizational culture and simultaneous work stress and partial positive and significant effect on employee performance at PT Serdang Jaya Perdana